Oxidative Stress and Antioxidants-A Critical Review on In Vitro Antioxidant Assays - Raghavendhar R. Kotha; Fakir Shahidullah Tareq; Elif Yildiz; Devanand L. Luthria (MDPI AG, 2022)
Antioxidants have been widely studied in the fields of biology, medicine, food, and nutrition sciences. There has been extensive work on developing assays for foods and biological systems. The scientific communities have well-accepted the effectiveness of endogenous antioxidants generated in the body. However, the health efficacy and the possible action of exogenous dietary antioxidants are still questionable. This may be attributed to several factors, including a lack of basic understanding of the interaction of exogenous antioxidants in the body, the lack of agreement of the different antioxidant assays, and the lack of specificity of the assays, which leads to an inability to relate specific dietary antioxidants to health outcomes. Hence, there is significant doubt regarding the relationship between dietary antioxidants to human health. In this review, we documented the variations in the current methodologies, their mechanisms, and the highly varying values for six common food substrates (fruits, vegetables, processed foods, grains, legumes, milk, and dairy-related products). Finally, we discuss the strengths and weaknesses of the antioxidant assays and examine the challenges in correlating the antioxidant activity of foods to human health.